Melihat Praktik Kerja Sama Usaha Cappucino Cincau A**** dan Analisis Penerapan Akad Syirkahnya - Magfur, Achmad; Hafidzi, Anwar; M. Hanafiah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract: Fresh, cold, sweet and portable drinks have become a trend among young people. Among them is Cappuccino Cincau, which was popular in the 2010s. But many disappeared and did not grow, as if following the seasons that passed before a year came together. But there is one that has survived until now, which is the object of the author's research, namely A**** Cappuccino Cincau. In total, there are already 21 outlets spread throughout South Kalimantan. Then how can this business grow sustainably? It turns out that one of them is the shirkah undertaken by the 3 owners, who even continue to maintain the clarity of the contract with the employees, and invite them to innovate, until they are financed through a new shirkah. Keywords: Shirkah, Islamic Economy, Banjarese Society. Abstrak: Minuman segar, dingin, manis, dan mudah dibawa, telah menjadi tren di kalangan kawula muda. Di antaranya adalah Cappucino Cincau yang sempat marak di tahun 2010an. Namun banyak yang hilang tidak tumbuh berkembang, seperti mengikuti musim yang berlalu sebelum satu tahun menyatu. Tetapi ada salah satu yang bertahan hingga kini, yang menjadi objek penelitian penulis, yakni Cappucino Cincau A****. Total sudah ada 21 outlet tersebar se-Kalsel. Lalu bagaimana usaha ini bisa tumbuh lestari? Ternyata di antaranya adalah jalinan syirkah yang dijalani 3 pemiliknya, yang bahkan terus memelihara kejelasan akad dengan para karyawan, dan mengajak mereka berinovasi, hingga dimodali lewat jalinan syirkah yang baru.